Antimicrobial peptides for bone tissue engineering: Diversity, effects and applications - Hao, Zhuowen; Chen, Renxin; Chai, Chen; Wang, Yi; Chen, Tianhong; Li, Hanke; Hu, Yingkun; Feng, Qinyu; Li, Jingfeng (Frontiers in Bioengineering and Biotechnology, 2022)
Bone tissue engineering has been becoming a promising strategy for surgical bone repair, but the risk of infection during trauma repair remains a problematic health concern worldwide, especially for fracture and infection-caused bone defects. Conventional antibiotics fail to effectively prevent or treat bone infections during bone defect repair because of drug-resistance and recurrence, so novel antibacterial agents with limited resistance are highly needed for bone tissue engineering. Antimicrobial peptides (AMPs) characterized by cationic, hydrophobic and amphipathic properties show great promise to be used as next-generation antibiotics which rarely induce resistance and show potent antibacterial efficacy. In this review, four common structures of AMPs (helix-based, sheet-based, coil-based and composite) and related modifications are presented to identify AMPs and design novel analogs. Then, potential effects of AMPs for bone infection during bone repair are explored, including direct sterilization, anti-biofilm, immunomodulation and regenerative properties. Moreover, we present distinctive applications of AMPs for topical bone repair, which can be either used by delivery system (surface immobilization, nanoparticles and hydrogels) or used in gene therapy. Finally, future prospects and ongoing challenges are discussed.